Bilateral spontaneous rupture of anterior lens capsules in a middle-aged woman - Chandrakanthan, Hemalatha; Hamzah, Norhafizah; Ismail, Shatriah (Dove Medical Press, 2012)
Hypermature cataracts are commonly seen in developing countries. Spontaneous rupture of the anterior capsule, resulting in dislocation of the lens nucleus into the anterior chamber, presents rarely in hypermature cataracts. We describe a middle-aged woman who presented with spontaneous anterior dislocation of the nucleus in both eyes. The presence of calcification spots in the posterior capsule at the pupillary edge strongly suggested that our patient had hypermature cataracts. It is important to highlight this uncommon cause of nucleus dislocation in a patient with no previous history of ocular trauma.